Driving Economic Value: Assessing the Financial Impact of Dynamic Message Signs on Freeways - Abushattal, Mousa Ahmad; Alhomaidat, Fadi; Alsanat, Husam; Kwigizile, Valerian; Isaria Mwende, Sia (Salehan Institute of Higher Education, 2025)
Dynamic Message Signs (DMSs) are an integral feature of any Intelligent Transportation System (ITS), providing drivers with real-time information such as travel time, incidents, routes, and weather conditions. This study aims to estimate the economic impacts associated with DMS use for route choice, weather advisories, and work zone management on freeways. Several freeway locations with varying levels of traffic congestion were selected to ensure a comprehensive evaluation under diverse conditions. Travel time savings and speed reductions were used as performance metrics to assess Benefit-Cost Ratios (BCRs) for each application. The findings show that DMSs yield substantial economic advantages across all use cases. For route guidance messages with a 35% diversion rate, the BCR was 1.032, indicating a cost-effective investment. Weather advisory messages recommending speed reduction achieved a notably higher BCR of 6.0, reflecting strong safety and financial benefits. Work zone applications using Portable Changeable Message Signs (PCMS) projected a BCR of 1.22. This study offers a data-driven justification for DMS deployment and contributes to the literature by focusing on financial performance, supporting strategic investment decisions beyond qualitative or operational assessments.